Penyuluhan Kepada Remaja Putri Untuk Meningkatan Pengetahuan Dan Sikap Terhadap Konsumsi Tablet Tambah Darah - Muhammad Irwan Setiawan; Lenny Indah Cahyani; Fajar Adi Mulya; Imilda Safitri; Isnawati Isnawati; Ladyqia Cintana Pinkan; Lintang Khairana Abdullah; Mauliana Mauliana; Ni'ma Farida Fasya; Noni Rianti; Noor Thaibah; Rahmayolanda Dalimo; Rifaldi Rifaldi; Sylva Patria; Yasmine Puspitasari (Jurnal Pengabdian Ilmu Kesehatan, 2023)
Iron deficiency anemia is a health problem experienced by many adolescent girl. Iron deficiency anemia will affect the learning progress of adolescent girls. Regularly consuming Blood Supplement Tablets (BST) can prevent and control iron deficiency anemia. The low coverage of BST consumption in the South Banjarbaru Public Health Center working area only reached 3.79%. Behavior change is implemented with counseling. Behavior change can be achieved by the intervention of behavioral predisposing factors. The purpose of counseling is to improve the knowledge and attitude of the target adolescent girls. Counseling was conducted online using the WhatsApp group platform and Zoom meeting. The application of the method through discussion with peer counselors, discussion, and question and answer. Participants of the counseling consisted of 30 adolescent girls from RT 003-005 RW 004 Guntung Paikat Subdistrict. Counseling media used PowerPoint slides and e-leaflet. The response of counseling participants was very enthusiastic about participating in the activity. The evaluation results showed a significant increase in knowledge (p-Value = 0,007) and attitude (p-Value = 0,0001) toward the consumption of Blood Supplement Tablets. Health promotion programs are expected to be carried out on a sustainable level to change behavior in consuming blood supplement tablets.